“Isolation and Genomic Analysis of an Intracellular Mycobacterium gordonae from a Free-Living Acanthamoeba sp. in a Hospital Environment in Lima, Peru “ - Cabello-Vílchez, Alfonso M. (2022)
“Mycobacterium gordonae is a nontuberculous mycobacterium found in diverse environments and is considered an opportunistic pathogen in immunocompromised patients. We report the draft genome sequence of a Mycobacterium gordonae strain isolated from a free-living amoeba found in a nosocomial environment in Lima, Peru.“